2014
DOI: 10.1186/ar4613
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of viral interleukin-10 with an antibody fragment specific to damaged arthritic cartilage improves its therapeutic potency

Abstract: IntroductionWe previously demonstrated that a single-chain fragment variable (scFv) specific to collagen type II (CII) posttranslationally modified by reactive oxygen species (ROS) can be used to target anti-inflammatory therapeutics specifically to inflamed arthritic joints. The objective of the present study was to demonstrate the superior efficacy of anti-inflammatory cytokines when targeted to inflamed arthritic joints by the anti-ROS modified CII (anti-ROS-CII) scFv in a mouse model of arthritis.MethodsVi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…The resulting fusion protein was able to inhibit disease progression in a mouse model of antigen-induced arthritis. Similar results were obtained by combining the antibody to the soluble portion of mTNFRII receptor fused to an Fc moiety [52,69].…”
Section: Preclinical Studies With Immunocytokines For Nononcological supporting
confidence: 70%
“…The resulting fusion protein was able to inhibit disease progression in a mouse model of antigen-induced arthritis. Similar results were obtained by combining the antibody to the soluble portion of mTNFRII receptor fused to an Fc moiety [52,69].…”
Section: Preclinical Studies With Immunocytokines For Nononcological supporting
confidence: 70%
“…The major difficulty seems to be the administration of IL-10 and calculation of its effective dosage in vivo. Targeted gene therapy might offer an effective approach, which allows a disease-regulated overexpression of IL-10 within the damaged cartilage joint 44,45 . Another promising strategy might be the administration of IL-10 in in vitro tissue engineering protocols since Tsuchida et al revealed that expanded chondocytes have impaired ability to produce IL-10 in vitro 30 .…”
Section: Discussionmentioning
confidence: 99%
“…We have produced and characterized an antibody that is specific to CII post-translationally modified by oxidants (anti-ROS-CII). This unique antibody has been validated in a series of studies demonstrating strong immunostaining on arthritic but not healthy cartilage, specific targeting to arthritic joint in vivo, and attenuation of knee inflammation by drug targeted by anti-ROS-CII (28,31). Once grafted onto EV, the anti-ROS-CII antibody acted as an arthritic cartilage-specific navigator, leading to an accumulation of EV selectively to arthritic joints with a peak at 18 h post-i.v.…”
Section: Discussionmentioning
confidence: 99%